2010
DOI: 10.1038/nnano.2009.457
|View full text |Cite
|
Sign up to set email alerts
|

Engineered biological nanofactories trigger quorum sensing response in targeted bacteria

Abstract: Biological nanofactories, which are engineered to contain modules that can target, sense and synthesize molecules, can trigger communication between different bacterial populations. These communications influence biofilm formation, virulence, bioluminescence and many other bacterial functions in a process called quorum sensing. Here, we show the assembly of a nanofactory that can trigger a bacterial quorum sensing response in the absence of native quorum molecules. The nanofactory comprises an antibody (for ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 25 publications
0
86
0
Order By: Relevance
“…Certainly, among the beneficial phenotypes attributed to QS, which could also be referred to as the 'currency' of the public good, are bioluminescence (Bassler et al, 1994), virulence (Zhu et al, 2002), biofilm formation (Balestrino et al, 2005;Gonzalez Barrios et al, 2006;Li et al, 2007), cell division, motility and cooperativity (Dandekar et al, 2012). We note that intentional rewiring these QS-regulated systems also benefits biotechnological applications, if not the microbes themselves (Fernandes et al, 2010;Tsao et al, 2010;Wu et al, 2013;Swofford et al, 2015;Thompson et al, 2015). It is therefore intriguing to consider what is the particular quorum and why was it reached.…”
Section: Introductionmentioning
confidence: 90%
“…Certainly, among the beneficial phenotypes attributed to QS, which could also be referred to as the 'currency' of the public good, are bioluminescence (Bassler et al, 1994), virulence (Zhu et al, 2002), biofilm formation (Balestrino et al, 2005;Gonzalez Barrios et al, 2006;Li et al, 2007), cell division, motility and cooperativity (Dandekar et al, 2012). We note that intentional rewiring these QS-regulated systems also benefits biotechnological applications, if not the microbes themselves (Fernandes et al, 2010;Tsao et al, 2010;Wu et al, 2013;Swofford et al, 2015;Thompson et al, 2015). It is therefore intriguing to consider what is the particular quorum and why was it reached.…”
Section: Introductionmentioning
confidence: 90%
“…Clearly, achieving such a goal of building nanofactories or nanomachines depends on our ability to link various functional units on demand and with high precision (1,3). It is surprising that current efforts in this promising field still rely on linking technologies that were invented several decades ago: biotin-streptavidin pairing, antibody-epitope recognition, and chemical linking through amino-or sulfhydryl groups (4). These approaches are often limiting because of the need to chemically modify recombinant proteins or the complexity of antibody-based techniques.…”
mentioning
confidence: 99%
“…With properly designed scaffolded multienzyme systems, one may accelerate conversion by taking advantage of the enhanced local intermediate concentrations resulting from the spatial control over enzyme organization (28). Finally, while this study demonstrated a new scaffoldin concept in yeast, such a technique should be equally applicable for improving protein display on other hosts as novel whole-cell biocatalysts, or even on nonbiological nanoparticles, to assemble nanofactories that comprise multiple functional modules (7).…”
Section: Discussionmentioning
confidence: 87%